Pengaruh Media Flashcard Terhadap Pengambilan Keputusan Pada Calon Akseptor KB Di Puskesmas Karangploso Kabupaten Malang - Safitri, Rani; Wijayanti, Tut Rayani Aksohini (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Flashcard media is a visual media that has several advantages. This media is used to find out and review and make decisions in choosing contraception This study aims to analyze whether there is an influence of Flashcard media on the decision making of prospective family planning acceptors. Research Methods This research uses a type of pre-experimental design research with a One Group Pretest – Posttest design approach. Using a purposive sampling technique with a total of 35 respondents. Results: Based on the results of the study, it was shown that more acceptors whose attitudes supported family planning after counseling with flashcard media (60%) took part in family planning compared to those who did not support it (17.1%). Data analysis used the Wilcoxon Signed Ranks Test statistic with a significant value of 0.002 (p 0.05), which means that there is an influence of Flashcard media as a method of decision making in family planning. Conclusion: The results of this study are expected to product innovation as a new method of family planning decision making.Flashcard or flashback card is a very powerful back and forth card used to remember and review and make decisions in the selection of contraceptives. The purpose of this study is to analyze whether there is an influence of Flashcard Media on decision making on prospective family planning acceptors. The type of research used is Pre-experimental design with the form of One Group Pretest - Posttest Sampling in this study total sampling. The total samples were 70 people, divided into 2 groups, namely the intervention group 35 samples and the control group 35 sample. Based on the results of the study, it was shown in the intervention group that after being given Flashcard media 27 samples had good knowledge level (77.14%), a small part of 2 sample had moderate knowledge level (17.5%) and a small percentage of 1 sample had less knowledge (5 ,36%). While in the control group, almost all of them with sufficient knowledge level were 34 samples (97%) and a small percentage of 1 samples with less knowledge (3%). Data analysis using the Wilcoxon test obtained a significance value of 0.006 (p 0.05), which means that there is an effect of giving the Flashcard method as a decision-making method in family planning. The results of this study are expected to be used as an innovation as a new method in making family planning decisions.